Age-related prevalence of dermatoscopic patterns of acral melanocytic nevi - Reiko Suzaki; Sumiko Ishizaki; Hitoshi Iyatomi; Masaru Tanaka (Mattioli1885, 2014)
The objective of this study was to evaluate the relation between age and dermatoscopic features of acral nevi. We evaluated 159 dermatoscopic images of melanocytic nevi from 146 individuals filed at the Dermatoscopy Outpatient Clinic of Tokyo Women's Medical University Medical Center East between April 2006 and March 2009. All images of melanocytic lesions on acral volar skin that showed a clear-cut dermatoscopic pattern of an acral nevus at the time of initial observation were included. The dermatoscopic patterns of all images were retrospectively examined in a blinded fashion according to the standard dermatoscopic classification criteria for acral melanocytic nevi. Images were classified using 15 structural variants of the parallel furrow pattern. These variants were then re-classified into two groups; the "single" line group and "double" line group. Patients of the double line group (age, 25.5 years) were significantly younger than those of the single line group (32.4 years). There was no significant difference in the age-related predominance between the solid line patterns and dotted line patterns. There was a significant age difference between patients with nevi showing the crista dotted pattern (mean age 24.9 years) and patients with nevi without the crista dotted pattern (mean age 34.6 years). We conclude that the double line variant of the parallel furrow pattern and crista dotted pattern, which probably correspond to the congenital type acral nevus, tend to be more common in young patients.